Delamination behaviors of an epoxy-impregnated REBCO pancake coil during a quench. (28th March 2023) - Liu, Donghui; Wei, Wanbo; Tang, Yunkai; Yong, Huadong; Zhou, Youhe
Highlights: The delamination is analyzed in an epoxy-impregnated pancake coil during a quench. The localized high-temperature gradients lead to delamination inside the coil. The delamination propagation is mainly determined by shear stress. Abstract: For the epoxy-impregnated high-temperature superconducting (HTS) REBa2 Cu3 O7-x (REBCO) magnets, the quench cannot be still avoided in the operation, which may induce the mechanical damage of the magnets and even burning out. In this research, an electromagnetic-thermo-mechanical coupling model is proposed to explore the delamination mechanisms of an epoxy-impregnated REBCO pancake coil during a quench, and thereinto, a cohesive zone model (CZM) based on the mixed-mode traction-separation law is used to simulate the onset and growth of the delamination. The numerical results indicate that the delamination of the coil is mainly concentrated in the quenching turns. The reason is that localized high-temperature gradients are generated in these turns due to the large temperature increase during a quench, and thus the accumulated stress induced by the thermal mismatch stress locally leads to the cracking of the interface between the superconducting layer and Hastelloy substrate. Meanwhile, the delamination onset of the coil is predicted by mixed-mode delamination according to the quadratic failure criterion, and the delamination propagation is mainly determined by shear stress. Up to now, the delamination mechanisms of the epoxy-impregnated pancake coil during a quench are clarified in detail, which is different from those during cooling down. To further understand the delamination behaviors of the epoxy-impregnated pancake coil during a quench, the effects of the location and height of the heater, and the thickness of the epoxy resin on the interface delamination failure are discussed in the paper.